Jenseits des Bürgerinvestors: Energiewende need Degrowth - Schachtschneider, Ulrich (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2016)
The German Energiewende (Energy Turn) in the electricity sector should be understood as ecological progress and as an example that current politics don’t necessarily all follow the neoliberal paradigm. However, the way of financing the Energiewende has lead to more inequality. Both the ongoing technological transformation following the idea of a Green New Deal and the paradigm „Bürgerenergiewende“ are not in danger with the new EEG regulation scheme. But in order to achieve a wider energy transition covering other important consumption sectors like housing or mobility as well as facilitating a decline of the energy demand, less economical and social inequality beyond citizens’ investment is needed.